2016
DOI: 10.1007/s00345-016-1833-3
|View full text |Cite
|
Sign up to set email alerts
|

Structured learning for robotic surgery utilizing a proficiency score: a pilot study

Abstract: Structured learning can be implemented in an academic robotic program with high levels of trainee and evaluator participation, encouraging both quantitative and verbal feedback. A proficiency assessment tool developed for step-specific proficiency has construct and concurrent validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The performing surgeon for each of the 10 surgical RARP steps, based on our institution's standardized structured learning curriculum , was catalogued prospectively. We collected synchronized video and APMs during RARP cases on the da Vinci Surgical System using the ‘dVLogger’ (Intuitive Surgical), a custom recording tool lent for the purposes of research.…”
Section: Methodsmentioning
confidence: 99%
“…The performing surgeon for each of the 10 surgical RARP steps, based on our institution's standardized structured learning curriculum , was catalogued prospectively. We collected synchronized video and APMs during RARP cases on the da Vinci Surgical System using the ‘dVLogger’ (Intuitive Surgical), a custom recording tool lent for the purposes of research.…”
Section: Methodsmentioning
confidence: 99%
“…The Global Evaluative Assessment of Robotic Skills (GEARS) tool, developed by Goh et al. , has been applied to urological assessments on multiple occasions , and has the strongest validity argument supporting its use in the assessment of robotic skill. Its generic framework has allowed it to become a widely accepted method of assessment across multiple procedures and even across specialties .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the validity evidence supporting the seven non-time-based technical skill assessment tools used in urological RAS. The Global Evaluative Assessment of Robotic Skills (GEARS) tool, developed by Goh et al [4], has been applied to urological assessments on multiple occasions [4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and has the strongest validity argument supporting its use in the assessment of robotic skill. Its generic framework has allowed it to become a widely accepted method of assessment across multiple procedures and even across specialties [4,15,19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this translates into a safer and effective way of surgical education. With the aim of further standardization, very recently Hung et al [20] reported improvements in training from a structured learning program in robotic surgery using proficiency scores. This has boosted the confidence of trainees' robotic skills.…”
Section: Mentoring and Proctoringmentioning
confidence: 99%